Multiple disparities: earning inequalities in Lisbon - Carmo, R. M. (2017)
The aim of this article is to analyse the way in which unequal salaries are related to spatial disparities within the city of Lisbon in a context of economic globalization. It will therefore compare the pay levels of the Lisbon's working population in the different parishes. Lisbon municipality stands out from the rest of Portugal because of workers' higher earnings there. However, the municipality has higher inequality levels than those of the country as a whole. These inequalities are not evenly distributed in the municipality’s parishes.